Integrated mRNA and microRNA profiling in lung tissue and blood from human silicosis - Zhang, Jingbo; Hu, Weijiang; Liu, Kai; Liu, Jie; Zheng, Yuxin; Sun, Xin; Mei, Liangying; Qian, Zushu; Sun, Qiangguo; Liu, Qiang; Wu, Zhijun; Zhang, Hengdong; et al. (The journal of gene medicine, 2023)
Background The overwhelming majority of subjects in the current silicosis mRNA and microRNA (miRNA) expression profile are of human blood, lung cells or a rat model, which puts limits on the understanding of silicosis pathogenesis and therapy. To address the limitations, our investigation was focused on differentially expressed mRNA and miRNA profiles in lung tissue from silicosis patients to explore potential biomarker for early detection of silicosis. Methods A transcriptome study was conducted based on lung tissue from 15 silicosis patients and eight normal people, and blood samples from 404 silicosis patients and 177 normal people. Three early stage silicosis, five advanced silicosis and four normal lung tissues were randomly selected for microarray processing and analyze. The differentially expressed mRNAs were further used to conduct Gene Ontology and pathway analyses. Series test of cluster was performed to explore possible changes in differentially expressed mRNA and miRNA expression patterns during the process of silicosis. The blood samples and remaining lung tissues were used in a quantitative real‐time PCR (RT‐qPCR) (RT‐qPCR). Results In total, 1417 and 241 differentially expressed mRNAs and miRNAs were identified between lung tissue from silicosis patients and normal people (p < 0.05). However, there was no significant difference in most mRNA or miRNA expression between early stage and advanced stage silicosis lung tissues. RT‐qPCR validation results in lung tissues showed expression of four mRNAs (HIF1A, SOCS3, GNAI3 and PTEN) and seven miRNAs was significantly down‐regulated compared to those of control group. Nevertheless, PTEN and GNAI3 expression was significantly up‐regulated (p < 0.001) in blood samples. The bisulfite sequencing PCR demonstrated that PTEN had significantly decreased the methylation rate in blood samples of silicosis patients. Conclusions PTEN might be a potential biomarker for silicosis as a result of low methylation in the blood. In the present study, we conducted a comprehensive analysis of differential mRNA and microRNA (miRNA) expression based on silicosis patients and normal people. Many differentially expressed mRNAs and miRNAs between their lung tissues were identified. There was no significant difference for most mRNA or miRNA expression between early stage and advanced stage silicosis lung tissues. In addition, PTEN and GNAI3 expression between lung tissues and blood samples suggested the opposite. PTEN was identified as potential biomarker for silicosis as a result of low methylation in the blood.